The structure of the death receptor 4–TNF-related apoptosis-inducing ligand (DR4–TRAIL) complex - Ramamurthy, Vidhyashankar (Acta Crystallogr F Struct Biol Commun, 2015)
The structure of death receptor 4 (DR4) in complex with TNF-related apoptosis-inducing ligand (TRAIL) has been determined at 3 Å resolution and compared with those of previously determined DR5–TRAIL complexes. Consistent with the high sequence similarity between DR4 and DR5, the overall arrangement of the DR4–TRAIL complex does not differ substantially from that of the DR5–TRAIL complex. However, subtle differences are apparent. In addition, solution interaction studies were carried out that show differences in the thermodynamics of binding DR4 or DR5 with TRAIL.